2004
DOI: 10.1152/ajpendo.00573.2003
|View full text |Cite
|
Sign up to set email alerts
|

Insulin stimulates fatty acid transport by regulating expression of FAT/CD36 but not FABPpm

Abstract: Because insulin has been shown to stimulate long-chain fatty acid (LCFA) esterification in skeletal muscle and cardiac myocytes, we investigated whether insulin increased the rate of LCFA transport by altering the expression and the subcellular distribution of the fatty acid transporters FAT/CD36 and FABPpm. In cardiac myocytes, insulin very rapidly increased the expression of FAT/CD36 protein in a time-and dose-dependent manner. During a 2-h period, insulin (10 nM) increased cardiac myocyte FAT/CD36 protein b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
99
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(102 citation statements)
references
References 36 publications
3
99
0
Order By: Relevance
“…Thiazolidinediones, a major new class of drugs to treat diabetes, up regulate CD36 in monocytes/macrophages, adipose and muscle (Wilmsen, Ciaraldi, Carter, Reehman, Mudaliar, & Henry, 2003, Kolak, et al, 2006, Hirakata, Tozawa, Imura, & Sugiyama, 2004,Llaverias, et al, 2006, and may therefore contribute to the insulin-sensitizing effects of these drugs as a result of plasma fatty acid clearance, but also potentially to atherosclerosis and obesity in these patients. Interestingly, glucose/insulin appears to increase CD36 expression (Sampson, Davies, Braschi, Ivory, & Hughes, 2003,Griffin, et al, 2001,Chabowski, et al, 2004,Chen, Yang, Loux, Georgeson, & Harmon, 2006, and because CD36 is expressed on tissues important in fatty acid metabolism (heart, skeletal muscle, fat, and in pathological states, liver) this may imply an important role for CD36 in insulin resistance (see later). Regulation of CD36 expression can be mediated both pre-and post-transcription.…”
Section: Cd36 Regulationmentioning
confidence: 97%
See 1 more Smart Citation
“…Thiazolidinediones, a major new class of drugs to treat diabetes, up regulate CD36 in monocytes/macrophages, adipose and muscle (Wilmsen, Ciaraldi, Carter, Reehman, Mudaliar, & Henry, 2003, Kolak, et al, 2006, Hirakata, Tozawa, Imura, & Sugiyama, 2004,Llaverias, et al, 2006, and may therefore contribute to the insulin-sensitizing effects of these drugs as a result of plasma fatty acid clearance, but also potentially to atherosclerosis and obesity in these patients. Interestingly, glucose/insulin appears to increase CD36 expression (Sampson, Davies, Braschi, Ivory, & Hughes, 2003,Griffin, et al, 2001,Chabowski, et al, 2004,Chen, Yang, Loux, Georgeson, & Harmon, 2006, and because CD36 is expressed on tissues important in fatty acid metabolism (heart, skeletal muscle, fat, and in pathological states, liver) this may imply an important role for CD36 in insulin resistance (see later). Regulation of CD36 expression can be mediated both pre-and post-transcription.…”
Section: Cd36 Regulationmentioning
confidence: 97%
“…In skeletal muscle, CD36 is important for fatty acid uptake, and its expression is regulated by both the environmental and cellular milieu (Chabowski, Gorski, Calles-Escandon, Tandon, & Bonen, 2006,Chabowski, et al, 2004,Chabowski, et al, 2005,Benton, Han, Febbraio, Graham, & Bonen, 2006,Cameron-Smith, et al, 2003. Studies in isolated cardiac muscle cells, using a specific CD36 inhibitor, sulfo-N-succinimidyl oleate, also showed that CD36 is likely the major membrane protein involved in fatty acid uptake (Koonen, et al, 2005).…”
Section: Other Functions Of Cd36 That May Impact Cardiovascular Diseasementioning
confidence: 99%
“…9 In addition, we have recently shown that insulin rapidly induces the expression of FAT/CD36 in cardiac myocytes and in the heart. 26 In humans, FAT/CD36 mRNA is increased in muscle during a hyperinsulinemic-euglycemic clamp, 27 and FAT/CD36 mRNA and insulin are correlated. 25 Thus, a circumstantial case can be made implicating increased concentrations of insulin in upregulating the expression of adipose tissue FAT/CD36.…”
mentioning
confidence: 98%
“…Altered FAT/CD36 expression is genetically linked with situations where insulin resistance and abnormal lipid metabolism occur in rats and humans (11,12). In humans, FAT/ CD36 is considered to be a significant factor in metabolic adaptation in diet and in susceptibility to certain abnormal situations related to diet (4,13,14).…”
mentioning
confidence: 99%
“…For example, in situations where lipid uptake is increased, such as in pre-adipocyte to adipocyte differentiation, during perinatal and postnatal heart development, in the skeletal muscle of diabetic experimental animals and in the heart of animals under fat-rich diet (7). Insulin and leptin regulate the expression of proteins associated with fatty acid binding and transportation (namely FAT, FABPpm, FATP and cytosolic FABPs) in various tissues through PPAR (peroxisome proliferator-activated receptors) (11,12,15).…”
mentioning
confidence: 99%